The Effectiveness of Using Webtoon Platform in Teaching Reading Comprehension Among Second Semester Students at Universitas Bhinneka PGRI in Academic Year 2023/2024 - Muhammad Miftahur Rozaq; Moh Choirul Huda (Concept: Journal of Social Humanities and Education, 2024)
English, a crucial global language, is essential in education and communication. In Indonesia, mastering English is vital, with the 2013 curriculum emphasizing the four skills: speaking, writing, listening, and reading. Reading comprehension, which integrates written content with prior knowledge, is particularly important. Various internal and external factors, such as word recognition, parental support, and educational media, impact students' reading comprehension. Digital media like Webtoon offer advantages such as accessibility and interactivity, making them valuable educational tools. This study examined how well the Webtoon platform taught reading comprehension to second-semester students at Bhinneka PGRI University's English Education Department in the academic year 2023–2024. Twenty-two individuals were chosen at random from the student body to make up the sample. This study employed a quantitative research approach with a pre-experimental design that included a one-group pretest, treatment, and post-test to determine the impact of Webtoon on reading comprehension skills. Using this strategy, the effectiveness of the intervention may be evaluated by contrasting pre- and post-test results. Students' reading comprehension scores increased dramatically after using Webtoon; on average, their scores went from 69.00 to 81.81. The data distribution was validated by normality tests, and a significant difference was found using a paired t-test (t(15) = -12.854, p < 0.001). These results showed how Webtoon improves reading comprehension and makes a good contribution to education by demonstrating creative uses of digital media in the classroom.Using this strategy, the effectiveness of the intervention may be evaluated by comparing pre- and post-test results.